Lymphadenectomy and Histologic Subtype Affect Overall Survival of Soft Tissue Sarcoma Patients With Nodal Metastases - Sawamura, Chigusa (Springer-Verlag, 2012)
BACKGROUND: Lymph node metastases in patients with soft tissue sarcomas are rare and these metastases are frequently associated with certain histologic subtypes. The survival is believed to be poor if lymph node metastases occur and the potential benefit of lymphadenectomy is unclear. QUESTIONS/PURPOSES: We determined whether lymph node metastases affect overall survival with regard to the status of lymphadenectomy, histologic subtypes, isolated or systemic metastasis, and the timing of presentation of lymph node metastases. METHODS: We retrospectively reviewed all 871 patients diagnosed with soft tissue sarcomas between 1983 and 2008 to determine whether they had lymph node metastases at diagnosis or subsequently and whether they had lymphadenectomy for treatment. Overall survival was assessed and the effect of prognostic variables was examined by a log rank test. RESULTS: Forty-nine of the 871 patients (6%) had lymph node metastases. The estimated 5-year survival rate for the group of 49 patients with lymph node metastases was 27%. Those who had lymphadenectomy had better survival at 1.5 years although there was no difference between those who did not undergo lymphadenectomy at 5 years. Patients with nonrhabdomyosarcoma had better overall survival than patients with rhabdomyosarcoma. Timing of development of lymph node involvement and whether lymph node metastases were an isolated site did not affect the overall survival. CONCLUSIONS: Overall survival of patients with lymph node metastases was related to histologic subtypes and patients with nonrhabdomyosarcoma had better survival than those with rhabdomyosarcoma. Resection of the metastatic lymph node did not improve long-term survival of patients with soft tissue sarcomas. LEVEL OF EVIDENCE: Level II, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.